2016
DOI: 10.1177/1049909116655767
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Residents Improve Knowledge, Skills, Attitudes, and Practice After a Clinical Curriculum With a Hospice

Abstract: Effective approaches to teaching attitudes, knowledge, and skills to resident physicians in primary care that can be implemented in any residency program are needed. We examined the feasibility and impact of a single palliative care residency curriculum, including a clinical rotation with a hospice program, across 5 cohorts of residents in 7 divergent primary care residency programs (both family medicine and internal medicine). The didactic content was drawn from the national Education for Physicians on End-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…From the literature, cohort studies exploring the transference of knowledge on symptom management and skills into the workplace are equivocal. 62,67 A few studies have evaluated the sustainability of improvements in physicians' practices or patient outcomes after a pain or non-pain…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…From the literature, cohort studies exploring the transference of knowledge on symptom management and skills into the workplace are equivocal. 62,67 A few studies have evaluated the sustainability of improvements in physicians' practices or patient outcomes after a pain or non-pain…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A 4-week hospice rotation improved resident confidence regarding palliative skills, and a 2-week required rotation showed improved communication skills. 8,9 A significant improvement in knowledge, attitudes, and skills was measured after residents completed a 4-week hospice rotation, and 50% of the residents surveyed perceived that the content was not available elsewhere in their training. 10 Another study found a significant improvement in all palliative care domains after residents completed a geriatrics rotation with palliative education built into the curriculum.…”
mentioning
confidence: 99%
“…Internationally, there is a lack of literature on the education of competencies in EoLC in both postgraduate trainees and especially in GP trainees: There are few published curricula such as from 2016 [37] and the questions of how and how much of teaching of EoLC is necessary during specialisation in general practice. If for example communicational skills in EoLC should be trained or if an intense course on EoLC is developed a well-planned curriculum based on previous experiences is mandatory [38,39]. A recent study, which was not available in 2016 when we had planned our study, presented a list of necessary learning objectives and goals for EoLC [40].…”
Section: Discussionmentioning
confidence: 99%